281 PREVALENCE OF STOPPFALL FALLS-RISK-INCREASING DRUGS (FRIDS) IN PATIENTS PRESENTING TO HOSPITAL WITH A FALL. (25th October 2022) - O'Donnell, D; Zainal, T; Malomo, K; Neasa, F; Briggs, R; Cunningham, C; Romero-Ortuno, R; Rice, C; Kenny, RA; Lavan, AH
Abstract: Background: Falls cause presentation and admission to hospital. Falls-Risk-Increasing-Drugs (FRIDs) are a modifiable risk factor. STOPPFalls criteria was developed, using an expert Delphi panel, to achieve consensus on a comprehensive list of FRIDs. The aim of this study was to identify the prevalence of STOPPFall PRIDs in patients presenting to hospital with falls and identify whether review by a specialist Falls and Syncope Service (FASS) reduces FRIDs. Methods: This was a retrospective observational study. Patients ≥65 years reviewed by the hospital FASS in the emergency department (over 6-months) and in house (over 2-months), were included. Medication appropriateness at admission and discharge were assessed using STOPPFall criteria. Ethical approval was received from the local research and innovation office (ref7013). Results: Of 156 patients, 87(55.8%) were ≥65 years; 46% female, mean age 78.1(SD7.5) years. The mean number of conditions was 4(SD4.4); the mean number of regular medications was 6.9(SD4.5). Reasons for referral to FASS included falls (34.5%), dizziness/near fall (35.6%), and transient loss of consciousness (29.9%). For 21.8% there was an associated injury; 11.5% a fracture. Thirty-seven (42.5%) had experienced at least one fall in the previous 12-months. Sixty-four (73.6%) were on ≥1 STOPPFall FRID. The most common STOPPFall FRID prescribed to older adults were diuretics (24.1%), anti-depressants (20.7%) and benzodiazepines/benzodiazepine-related drugs (13.8%). At least 1 STOPPFall FRID was stopped in 31.3%. The most commonly deprescribed STOPPFall FRIDs were diuretics (20%), alpha blockers (6%) and benzodiazepines/benzodiazepine-related drugs (4.7%). Adults <65years (n=69) were more likely to be prescribed a STOPPFall FRID at admission than older adults (≥65years); 88.4% vs 73.6%, p=0.021. Conclusion: STOPPFall FRIDs are prevalent in fallers of all ages. Even one review by a specialist FASS leads to medication optimization. The effectiveness of STOPPFalls criteria in the prevention of falls should be evaluated further in intervention studies.